Association of nutritional status and diet with the gut microbiome in acutely ill hospitalised older adults - Muñoz Fernandez, Shirley Steffany (2023)
Introduction - Ageing is characterised by changes associated with an increased risk of developing chronic diseases and syndromes, of which malnutrition is one of the most common in older adults. The gut microbiota has an important role in the host\'s health and is determined by several factors, including nutritional status and diet. Therefore, the gut microbiota may be associated with malnutrition and dietary intake in acutely ill older adults. Objectives - to identify- 1) the prevalence of malnutrition; 2) the association of malnutrition with the composition and metabolic potential of the gut microbiota and its impact on clinical outcomes; 3) the effect of habitual diet on the gut microbiota of acutely ill hospitalised older adults according to the nutritional status. Methods - a longitudinal analysis secondary to a prospective cohort was performed on 108 participants aged 65+ years old admitted to the hospital due to acute conditions. Clinical, demographic, nutritional, and anthropometric data and rectal swab samples were collected at admission and after 72 hours of hospitalisation. The food intake was estimated using the dietary history and the nutritional status diagnosed using the Global Leadership Initiative on Malnutrition (GLIM) criteria, preceded by the Mini-Nutritional Assessment Short-form (MNA-SF). Rectal swab samples were obtained to analyse the gut microbiota via 16S rRNA gene sequencing. The microbiota diversity, overall composition and differential abundances were calculated and compared between well-nourished and malnourished groups. Microbiome features potentially associated with malnutrition were selected by penalised models and confirmed by additive models. The prediction of clinical outcomes was investigated from the \"malnourished microbiota\" using decision trees. The dietary intake was explored through multivariate methods and investigated with the microbiota using tests of association and mediation analysis. Results - Malnourished patients (51%) had a different overall microbiota composition compared to well-nourished during hospitalisation (R= 0.079, p= 0.003). Severely malnourished (32.4%) showed a poorer diversity at admission (Shannon p= 0.012, Simpson p= 0.018) and after 72 hours (Shannon p= 0.023, Chao1 p= 0.008). Subdoligranulum, Lachnospiraceae NK4A136 group and Faecalibacterium prausnitzii, short-chain fatty acids producers, had significantly lower abundance and negative association with malnutrition, while Fusobacterium, Corynebacterium and Ruminococcaceae Incertae Sedis were highly increased and positively associated with malnutrition. Corynebacterium, Ruminococcaceae Incertae Sedis and the overall composition were important predictors of critical care in malnourished during hospitalisation. Malnourished patients had a significantly lower intake of plant protein, carbohydrates, dietary fibre, Fe, Mn, folate, campesterol, beta-sitosterol, and α-linolenic acid, and higher intake of Vitamin D. There were no significant correlations of nutrients, foods or food groups with the microbiota structure, but for individual taxa and α-diversity metrics. Mediation analysis revealed a significant indirect effect of the nutritional status on the differential abundance of several bacterial taxa partially mediated in a positive direction by dietary fibre, plant-based protein, onions, and olive oil, and negative by vitamin D. Conclusion - Malnourished patients had a significantly lower intake of key dietary compounds and substantial gut microbial disturbances during hospitalisation, pronounced in the severe stage. Some plant-based compounds might confer beneficial effects on the gut microbiota profile. A \"malnourished microbiota\" may be able to predict critical illness in hospitalised malnourished older patients. Bench-to-bedside investigations are necessary to confirm these findings.